ENHANCING LISTENING SKILLS THROUGH STORY-BASED ACTIVITIES FOR VOCATIONAL STUDENTS IN YOGYAKARTA - Wilanda Aziza; Tri Wahyuni Floriasti (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2024)
This research investigates the development of story-based listening activities for vocational students in Yogyakarta using the ADDIE model. The study involved sixty-six vocational students and employed qualitative and quantitative methods. The focus on vocational students is crucial because their learning needs are centred around acquiring practical, career-related language skills. Story-based activities and research instruments were designed to address real-world scenarios relevant to vocational education, ensuring the learning experience is both engaging and applicable to their future careers. Qualitative data from interviews, classroom observations, and open-ended questionnaires revealed that students found story-based activities engaging and motivating. Quantitative data from pre- and post implementation questionnaires and tests showed significant improvements in listening comprehension, with 63.6% of students reporting increased confidence in understanding native speakers. The story-based approach provided a practical and enjoyable learning experience, making it particularly suitable for vocational high school students who benefit from active and contextually relevant learning methods.